2021
DOI: 10.21873/anticanres.15317
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Cardiophrenic Lymph Node Status After Neoadjuvant Chemotherapy in Primary Advanced Ovarian Cancer

Abstract: Background/Aim: This study investigated the cardiophrenic lymph node (CPLN) status before and after neoadjuvant chemotherapy (NACT), as its presence seems to have a rather prognostic significance in patients with advanced ovarian cancer. Patients and Methods: The baseline computed tomography scans of 66 patients with advanced ovarian cancer primary treated with NACT between March 2015 and June 2020 were reviewed. A CPLN enlargement was defined as ≥5 mm. Results: 44% (n=29) of the patients had enlarged CPLNs; 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…More than 70% of OC patients were diagnosed as late stage because of the insidious progress and not obvious symptoms early, which leads to the 5-year survival rate is only 30% -40% [4]. The issue of LNM in OC has a particular interest among gynecological oncologists worldwide, because the LNM was with high occurrence and would affect the prognosis of OC [1,12,13,14]. Nasioudis et al have found that the rate of LNM was about 3.3% -14% in early OC and as high as 40% ~ 73.7% in late OC [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…More than 70% of OC patients were diagnosed as late stage because of the insidious progress and not obvious symptoms early, which leads to the 5-year survival rate is only 30% -40% [4]. The issue of LNM in OC has a particular interest among gynecological oncologists worldwide, because the LNM was with high occurrence and would affect the prognosis of OC [1,12,13,14]. Nasioudis et al have found that the rate of LNM was about 3.3% -14% in early OC and as high as 40% ~ 73.7% in late OC [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Enlarged cardiophrenic lymph nodes are found in 10.5-62% of patients with advanced epithelial ovarian cancer, depending on the radiological size classification of a pathological node. [10][11][12][13][14] There is no current consensus regarding which radiological short axis cardiophrenic lymph nodes length should be considered pathological, with current cut-off values varying from 5 to 10 mm. 10 11 13 15 16 This lack of standard classification makes prognostication and diagnosis challenging.…”
Section: Imagingmentioning
confidence: 99%